The listening tree - Lottridge, Celia Barker (Markham, Ont. : Fitzhenry & Whiteside, 2011)
When Ellen and her mother board with Aunt Gladys in the city, Ellen finds comfort in the old tree near her window, and realizes she must overcome her fears of the outside world when she overhears a disturbing plot.
Booklist
Bulletin (Center for Children's books)
School Library Journal
Booklist, April 2011
Bulletin (Center for Children's books), April 2011
Resource Links, April 2011
Keywords: Courage -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Self-esteem -- Juvenile fiction; Courage -- Fiction; Interpersonal relations -- Fiction; Self-esteem -- Fiction; Courage -- Fiction; Interpersonal relations -- Fiction; Self-esteem -- Fiction